The Journal of Engineering Education It's Joureny from Issue No. 1 to 100 and 106 and Beyond - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2014)
The article presents the story of "Journal Engineering Education" which was published from Pune from 1986 to 2014 under my editorship. I started this Journal and was editor for all the issues, from Issue No. 1 to Issue No. 106. I may also mention here that , this also is the story of my own dream --- to become a Professor and also a Journalist --- and how I realized this dream. It describes why and how a journal started in 1986, and how it continued publication, involving 14 special issues which was then, important and burning issues of Engineering Education in India. At the end of 26 years of publishing this Journal, with my advancing age - ------ I am now 88++plus years ------- I felt the necessity of handing over this Journal to the environment with their new dreams. Fortunately, I could find such a younger team who have taken up this Journal activity and are even elevating the Journal to International standards and is well set on the never ending path of global Quality and Excellence.The new team consist of Dr. Mrs. Sushama Kulkarni, Director, Rajaram Bapu Institute of Technology, Islampur, Dist. Sangali, Maharashtra, India, and her colleagues.